Pengembangan Masyarakat Terdampak Proyek Nasional Strategis JIIPE pada Komunitas Poor Headed Female (Kepala Keluarga Perempuan Miskin) melalui Kegiatan Perekonomian di Kawasan Industri Gresik - Juliyani, Erly (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Poverty is a common thing that occurs in every community. Women-headed families are generally in a state of deprivation. Karangrejo village subdistrict. Manyar district. Gresik is a Jiipe National Strategic Project (PNS) area where the majority of the people are housewives whose livelihoods are uncertain, sometimes as fishermen, laborers from fish ponds and often have no income. Empirically, there are ± 50 headed by women who are in a state of deprivation or poverty (poor headed women) whose background is the death of their husband. Insufficient human resources are the main factor in causing poverty among heads of poor families in Karangrejo village, sub-district. Manyar district. Gresik. So that the resilience and economic coping strategies they apply are able to maintain their families. Problems arise when there is a big harvest in several areas in East Java, especially Gresik Regency. Efforts to utilize this fish so that it has a high selling value is by processing the milkfish into a semi-finished product, namely batari (milkfish with thorns removed). The price of thorn-pulled milkfish has a very economical price, in traditional markets the small size can reach IDR 10,000/head with a net weight of 130 – 180 grams, while the large size with a net weight of 330-380 grams can reach IDR 20,000/head. The location for implementing community service is Karangrejo village, a village where the majority of the population are pond farmers, approximately 75% are pond farmers and 25% are factory workers. The aim of implementing this community service activity is first to open business opportunities and employment opportunities. Second, foster an entrepreneurial spirit in the community and third, produce processed thorn-pulled milkfish products. Through coaching in this community service program, it is hoped that mothers affected by the Jiipe national strategy project can utilize all parts of milkfish whose selling price is low into processed products with high economic value. So that farmers and village residents will benefit